2020
DOI: 10.1002/csr.1893
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering sustainability: An advancement in corporate social responsibility conceptualization

Abstract: In order to meet the versatile expectations of stakeholders, enterprises need philanthropic representation in communities. This research aims to empirically investigate the employee-specific viability of potential philanthropic initiatives of wholly foreign-owned enterprises to delineate volunteering sustainability. It covers five potential internal and external volunteering initiatives-matchmaking, marriage arrangement, and poverty alleviation through skill development, anti-sexual harassment awareness campai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…We put forth the limitations confronted in this conceptual paper with recommendations and plans particularly for continuous improvement in the next steps and generally for other researchers interested in finding the ways to curb bullying. Since our research focuses on the well‐being of individuals, the knowledge can be advanced in the areas of cross‐cultural management and social responsibility (Farooq, Liu, Fu & Hao, 2020) which may also play important role in human development and to alleviate bullying; the present paper has identified this element but separate research is required to explore various facets of cross‐cultural management to find its influence in subject perspective. In certain circumstances of power and politics at workplace and group conspiracies, subordinates may also act as the bullies to upward stream.…”
Section: Conclusion and Methodological Directions For Future Researchmentioning
confidence: 99%
“…We put forth the limitations confronted in this conceptual paper with recommendations and plans particularly for continuous improvement in the next steps and generally for other researchers interested in finding the ways to curb bullying. Since our research focuses on the well‐being of individuals, the knowledge can be advanced in the areas of cross‐cultural management and social responsibility (Farooq, Liu, Fu & Hao, 2020) which may also play important role in human development and to alleviate bullying; the present paper has identified this element but separate research is required to explore various facets of cross‐cultural management to find its influence in subject perspective. In certain circumstances of power and politics at workplace and group conspiracies, subordinates may also act as the bullies to upward stream.…”
Section: Conclusion and Methodological Directions For Future Researchmentioning
confidence: 99%
“…Instead of relying on government embargos on any unethical business by the supplier, for instance, illegal harvesting of timber being supplied, corporations can themselves be discerning in choosing such suppliers and encouraging those who also comply with seventh P “Participation” (Farooq et al, 2020) of extended bottom line (profit, people, planet, prosperity, peace, and partnership). The seventh P, participation (Farooq et al, 2020) conforms to the concept of voluntary sustainability through employees which was introduced by Bennett (2018). Now, after the stunning transition, CSR has been accepted as the fundamental strategic priority of different levels of businesses.…”
Section: Analytical Findings Of Textual Reviewmentioning
confidence: 99%
“…While institutional theory explains that institutional practices and external environment influence organizational behaviors (DiMaggio & Powell, 1983), institutional pressures are not the sole source of social and environmental‐friendly motivation for social responsibility of businessmen and entrepreneurs (Farooq et al, 2019; Newth, 2016). With the intrinsic motivation of employees and decision makers, many corporate social initiatives (CSIs) are taken on voluntary basis because intrinsic motivation in particular corporate initiatives has a positive relationship with affective commitment of internal stakeholders (Farooq, Liu, Fu, & Hao, 2020; Hao, Farooq, & Zhang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2016) said that organizations have become superior economic institutions of the world from respective ambiguity over the last one and a half century. Prior studies also indicated that in modern business world organizations are interested in ethics and values are considered an important element of success (Solomon, 2016;Farooq et al, 2020). Moreover, organizational values are continually fluctuating because of various elements.…”
Section: Introductionmentioning
confidence: 99%
“…Although, competitive advantage (CA) is the organizational ability to consume its rare resources and skills in the selection and execution of schemes (Shaukat, Qiu & Trojanowski, 2016). CA supports organizations to yield higher profits as compared to their competitors, increase the market share and lead in the industry.The CSR is a valuable approach which helps the organizations in getting a competitive advantage over its rivals and researchers are interested in this topic (Farooq et al, 2020, Noor et al, 2020.…”
Section: Introductionmentioning
confidence: 99%